Home

Maths

Algebra

Composite and inverse functions - Higher

Composite and inverse functions - Higher

Select Lesson

Exam Board

Select an option

Explainer Video

Loading...
Tutor: Bilal

Summary

Composite and inverse functions

​​In a nutshell

Functions take an input, perform an operation and then produce an output. Functions can be represented diagrammatically with a function machine or algebraically with f(x)f(x) notation. 

Once a function is written in function notation, it is possible to perform calculations to find the output, find composite functions and inverse functions. A composite function is a combination of two different functions, and an inverse function performs the inverse operation to the original function.



Function machines

Function machines are used to apply operations to an input to obtain an output. The input can be a number, a variable or even an expression. The function machine is represented in a diagram and can be written using f(x)f(x) notation.


Example 1

Here is a function machine, find the output for the inputs 55, xx and y+1y+1.

input×2+1outputinput \longrightarrow \fcolorbox{black}{white}{$\times 2$}\longrightarrow\fcolorbox{black}{white}{$+1$}\longrightarrow output​​


5×2+1115 \longrightarrow \fcolorbox{black}{white}{$\times 2$}\longrightarrow\fcolorbox{black}{white}{$+1$}\longrightarrow \underline{11}​​

x×2+12x+1x \longrightarrow \fcolorbox{black}{white}{$\times 2$}\longrightarrow\fcolorbox{black}{white}{$+1$}\longrightarrow \underline{2x+1}​​

y+1×2+12(y+1)+1=2y+3y+1 \longrightarrow \fcolorbox{black}{white}{$\times 2$}\longrightarrow\fcolorbox{black}{white}{$+1$}\longrightarrow 2(y+1)+1 = \underline{2y+3}​​


Example 2

Write the function machine using f(x)f(x) notation.

x2squareyx \longrightarrow \fcolorbox{black}{white}{$-2 $} \longrightarrow\fcolorbox{black}{white}{$square$}\longrightarrow y​​


f(x)=(x2)2\underline{f(x)=(x-2)^2}​​



f(x)f(x) notation

A function written algebraically in f(x)f(x) notation can be used to calculate an output from an input. It is also possible to find the input given an output. 


Example 3

Find the outputs for the function f(x)=x23f(x)=x^2-3​ with inputs 2,w2, w and y+1y+1.

f(x)=x23f(2)=223=1f(w)=w23f(y+1)=(y+1)2+3=y2+2y+4\begin{aligned}f(x)&=x^2-3 \\f(2) &= 2^2-3 = \underline{1} \\f(w)&=\underline{w^2-3} \\f(y+1) &= (y+1)^2+3 = \underline{y^2+2y+4}\end{aligned}​​


Example 4

For f(x)=2x3f(x)= 2x-3, find the input when the output is 77.


Make the function equal to 77 and then solve for xx.

f(x)=2x3=72x3=72x=10x=5\begin{aligned}f(x)=2x-3&=7 \\2x-3&=7 \\2x&=10 \\\end{aligned}\\\underline{x=5}​​



Composite functions

Composite functions consist of two functions combined together. The output of one function machine is used as an input for another function. The order of applying the functions matters. If an input is put through a function f(x)f(x) then the output is put through g(x)g(x), the composite function is called gf(x)gf(x).


xf(x)g(x)yx \longrightarrow \fcolorbox{black}{white}{$f(x)$}\longrightarrow \fcolorbox{black}{white}{$g(x)$}\longrightarrow y     is the same as     xgf(x)yx \longrightarrow \fcolorbox{black}{white}{$gf(x)$}\longrightarrow y


To find the composite function, substitute the inner function, which is f(x)f(x)​ in the above example, into the outer function g(x)g(x).


Example 5

Find the composite function fg(x)fg(x) for the functions

f(x)=x2 and g(x)=x5f(x) = x^2 \space and \space g(x)=x-5​​

Substitute the inner function g(x)g(x) into f(x)f(x) to give

fg(x)=(x5)2\underline{fg(x)=(x-5)^2}​​



Inverse functions

An inverse function f1(x)f^{-1}(x) performs the inverse operation to f(x)f(x). If f(x)f(x) takes an input xx to calculate an output yy, then the inverse operation will take the value of yy as an input and give the output as xx.

xf(x)yxf1(x)y\begin{aligned}x \longrightarrow &\fcolorbox{black}{white}{$f(x)$} \longrightarrow y \\\\x \longleftarrow &\fcolorbox{black}{white}{$f^{-1}(x)$} \longleftarrow y \\\end{aligned}​​


To find an inverse function, rearrange the function for xx and then swap xx and yy. Then rename the function to f1(x)f^{-1}(x).


Example 6

Find the inverse function for

f(x)=5x3f(x)=5x-3​​


Write the equation as 

y=5x3y=5x-3​​


Rearrange for xx.

y=5x3y+3=5xy+35=xx=y+35\begin{aligned}y&=5x-3 \\y+3 &=5x \\\frac {y+3} 5 &= x \\x &= \frac {y+3} 5\end{aligned}​​


Swap the yy for xx and rename the function to f1(x)f^{-1}(x).

f1(x)=x+35\underline{f^{-1}(x)=\frac{x+3}{5}}​​


Create an account to read the summary

Exercises

Create an account to complete the exercises

FAQs - Frequently Asked Questions

What is an inverse function?

What is a composite function?

What is a function in maths?

Beta

I'm Vulpy, your AI study buddy! Let's study together.